Scientific research activity and GDP: An analysis of causality based on 144 countries from around the world - Wiesław Dębski; Bartosz Świderski; Jarosław Kurek (Contemporary Economics, 2018)
Using the Granger methodology, this paper presents the causal relationship between scientific research activity, expressed as the number of significant publications, and gross domestic product (GDP). With causality tests, this relationship is investigated from two points of view: for each individual country (144 were selected) and for each specific academic field (28 were selected). Considering annual data from 1996 to 2012, two hypotheses are tested. The first suggests that scientific research activity in a given country has a significant effect on GDP; the second verifies how much each specific field of scientific research activity affects this growth. Our research confirmed the existence of this relationship for a relatively large number of countries, especially highly developed countries and those with a high potential both in the fields of scientific research activity and in GDP. Moreover, this study identifies the most significant fields of this activity that affect GDP. Additionally, the article includes an empirical study regarding how information related to the number of significant scientific publications influenced the quality of Polish GDP forecasts for 2011-2012.
Keywords: O10; O40; 330; Granger causality; weighted least squares method; number of significant publications; GDP; forecast quality